Characterization of human DNGR-1(+) BDCA3(+) leukocytes as putative equivalents of mouse CD8α(+) dendritic cells - Poulin, Lionel Franz (The Rockefeller University Press, 2010)
In mouse, a subset of dendritic cells (DCs) known as CD8α(+) DCs has emerged as an important player in the regulation of T cell responses and a promising target in vaccination strategies. However, translation into clinical protocols has been hampered by the failure to identify CD8α(+) DCs in humans. Here, we characterize a population of human DCs that expresses DNGR-1 (CLEC9A) and high levels of BDCA3 and resembles mouse CD8α(+) DCs in phenotype and function. We describe the presence of such cells in the spleens of humans and humanized mice and report on a protocol to generate them in vitro. Like mouse CD8α(+) DCs, human DNGR-1(+) BDCA3(hi) DCs express Necl2, CD207, BATF3, IRF8, and TLR3, but not CD11b, IRF4, TLR7, or (unlike CD8α(+) DCs) TLR9. DNGR-1(+) BDCA3(hi) DCs respond to poly I:C and agonists of TLR8, but not of TLR7, and produce interleukin (IL)-12 when given innate and T cell–derived signals. Notably, DNGR-1(+) BDCA3(+) DCs from in vitro cultures efficiently internalize material from dead cells and can cross-present exogenous antigens to CD8(+) T cells upon treatment with poly I:C. The characterization of human DNGR-1(+) BDCA3(hi) DCs and the ability to grow them in vitro opens the door for exploiting this subset in immunotherapy.